Alzheimer Cells on Their Way to Derailment Show Selective Changes in Protein Quality Control Network - Koopman, Margreet B.; Rüdiger, Stefan G. D. (Frontiers in Molecular Biosciences, 2020)
Alzheimer’s Disease is driven by protein aggregation and is characterised by accumulation of Tau protein into neurofibrillary tangles. In healthy neurons the cellular protein quality control is successfully in charge of protein folding, which raises the question to which extent this control is disturbed in disease. Here we describe that brain cells in Alzheimer’s Disease show very specific derailment of the protein quality control network. We performed a meta-analysis on the Alzheimer’s Disease Proteasome database, which provides a quantitative assessment of disease-related proteome changes in six brain regions in comparison with age-matched controls. We noted that levels of all paralogues of the conserved Hsp90 chaperone family are reduced, while most other chaperones – or their regulatory co-chaperones - do not change in disease. The notable exception is a select group consisting of the stress inducible HSP70, its nucleotide exchange factor BAG3 – which links the Hsp70 system to autophagy - and neuronal small heat shock proteins, which are upregulated in disease. They are all members of a cascade controlled in the stress response, channelling proteins towards a pathway of chaperone assisted selective autophagy. Together, our analysis reveals that in an Alzheimer’s brain, with exception of Hsp90, the players of the protein quality control are still present in full strength, even in brain regions most severely affected in disease. The specific upregulation of small heat shock proteins and HSP70:BAG3, ubiquitous in all brain areas analysed, may represent a last, unsuccessful attempt to advert cell death.